Atypical Black Leader Emergence: South African Self-Perceptions - Myeza, Angel; April, Kurt (Frontiers in Psychology, 2021)
The research aimed to gain understanding of the self-perceptions of black professionals in relation to business leadership, and how these self-perceptions influenced their behaviours, aspirations and self-perceived abilities in leadership positions. The study was specifically focused on black South African professionals. Black professionals were found to exhibit signs of deep-rooted pain, anger and general emotional fatigue stemming from workplace-, socio-economic- and political triggers that evoked generational trauma and overall negative black lived experiences. The negative lived experiences could have led to racial identity dissonance and, in extreme cases, complete racial identity disassociation. Moreover, black professionals were found to display symptoms of ‘survivor guilt’, stemming from the shared history of oppression amongst black people in South Africa. The ‘survivor guilt’ contributed towards a profound sense of shared responsibility and purpose to change the circumstances, experiences and overall perceptions about the capabilities of black professionals. Results showed that upbringing, determination, resilience, black support networks, and black leadership representation within organisational structures were important ingredients that positively contributed to the leadership aspirations and success of black professionals. The research discovered that, in some cases, black professionals leveraged white relationships to propel their careers forward, however, this practice reportedly resulted in the black professionals experiencing feelings of self-doubt in their own abilities. Self-doubt, also found to be a result of historical oppression, could have and have been shown to eventually lead to self-deselection, negatively impacting the aspirations and career advancement prospects of black professionals in organisational leadership. Furthermore, the research found that black leaders believed that their blackness, specifically, its unique texture of experiences and history in South Africa, provided them with superior empathetic leadership abilities towards other black employees. Black leaders frequently highlighted the distinctive values of ubuntu as the cornerstone of their leadership approach. In addition, it was found that black professionals also considered their blackness, particularly the shade of their skin, to detract from their leadership capability, as it reduced the odds of being authorised as natural leaders, thus fortifying a skewed self-perception of their own leadership capabilities.